Subjects of natural monopolies - Aziza Ibragimova (Genius Publishing Group, 2022)
The issue of legal status of the subjects of natural monopolies is one of the important problems of modern competition law. In this paper is dedicated to the analyze of the subjects of natural monopolies. Uzbek legislation on the topic is compared with the norms of legislation of other countries. Specific characteristics of these subjects are classified and defined.
Keywords: natural monopolies; competition; subjects of natural monopolies; entrepreneurs